The Borrowers afloat - Norton, Mary.; Krush, Beth.; Krush, Joe. (San Diego : Harcourt Brace Jovanovich, 1990)
The Borrowers, a family of miniature people, journey down a drain, live briefly in a teakettle, and are swept away in a flood before finding a new home. Sequel to "The Borrowers Afield."
"An Odyssey classic."
Keywords: Fantasy